Inversión en publicidad en el sector comercial de la provincia de Loja y su relación con la rentabilidad y liquidez - Carrión Sarango, Karen Adriana (2023)
Nowadays, there are great opportunities for commercial companies through investment in advertising, playing an important role since they have become a strategic tool for these organizations to maximize their income. The present research work focuses on analyzing the investment in advertising in the commercial sector in Loja province; and its relationship with profitability and liquidity, highlighting that not all organizations have the initiative to carry out adequate marketing of their products. The study data come from the Superintendence of Companies, Securities and Insurance; the methodology was deductive and inductive with a qualitative and quantitative approach applying Pearson's correlation; the study population corresponds to large commercial companies in the province of Loja. Regarding the results obtained, the correlation with ROE profitability is positive and significant; however, the relationship of ROA is not significant, because this indicator depends on the investments made or assets financed with own or other people's resources. In relation to liquidity, it was found that it is not significant, since this indicator does not depend on advertising investment. Finally, it is concluded that commercial companies, by not prioritizing investment in promotion and advertising, have a low return on equity, due to the fact that their products are not positioned in the market and their turnover levels are not as expected; and with no impact on liquidity.